2015
DOI: 10.1016/j.cvfa.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Bovine Keratoconjunctivitis (Pinkeye)

Abstract: Key Points• Effective treatment of pinkeye requires accurate diagnosis• Antibiotic treatment can the shorten healing time• Multiple routes of antibiotic delivery can be effective• Efforts to develop herd preventive strategies must involve considerations of risk factors Video of classical signs of Infectious bovine keratoconjunctivitis accompanies this article. AbstractAs with many livestock diseases, the most successful efforts to control (Infectious bovine keratoconjunctivitis) IBK include multiple facets of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 32 publications
(34 reference statements)
0
26
1
Order By: Relevance
“…Diagnosis of lymphoma and melanoma was based on histopathology. Diagnosis of ruptured globe secondary to infectious bovine keratoconjunctivitis (IBK) was based on history and ocular signs consistent with IBK (photophobia, blepharospasm, increased lacrimation, corneal edema, corneal ulceration, and corneal stromal abscess) . Diagnosis of ruptured globe due to trauma was based on history and ocular examination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of lymphoma and melanoma was based on histopathology. Diagnosis of ruptured globe secondary to infectious bovine keratoconjunctivitis (IBK) was based on history and ocular signs consistent with IBK (photophobia, blepharospasm, increased lacrimation, corneal edema, corneal ulceration, and corneal stromal abscess) . Diagnosis of ruptured globe due to trauma was based on history and ocular examination.…”
Section: Methodsmentioning
confidence: 99%
“…Exenteration is a relatively simple surgical procedure that can alleviate pain associated with ocular diseases and may prevent osteomyelitis of the bony orbit or progression of neoplasia . Indications for exenteration in cattle include severe trauma to the eye with loss of globe contents, ocular neoplasms, septic panophthalmitis, phthisis bulbi with associated conjunctivitis, enlarged painful glaucomatous eyes, and rupture of the globe secondary to infectious keratoconjunctivitis . In the majority of cases in cattle, there is no need to preserve the globe for esthetic considerations when orbital surgery is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-negative bacterium Moraxella bovis is suggested as the causative agent of IBK [5], although recent studies have shown that Moraxella bovoculi , originally identified in 2002 and shown to be distinct from M. bovis , may also be associated with IBK [6, 7]. A disease similar to IKC has also been documented in sheep and goats [8, 9], as well as in a wide range of wild animal species, such as moose ( Alces alces ), mule deer ( Odocoileus hemionus ), ibex ( Capra ibex ), chamois ( Rupicapra rupicapra ), roe deer ( Capreolus capreolus ) and red deer ( Cervus elaphus ).…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in electrophoretic mobility of mutants between Mb25 and Epp63 in the present study suggests that at least for these genes, the associated structures are conserved in these strains. Another related bacterium, M. bovoculi, has relatively recently been recognised as another causative agent of IBK (see [18] for review).…”
Section: Losmentioning
confidence: 99%